The Association Between Sleep Disorders and Incidence of Dry Eye Disease in Ningbo: Data From an Integrated Health Care Network - Zheng, Qinxiang; Li, Saiqing; Wen, Feng; Lin, Zhong; Feng, Kemi; Sun, Yexiang; Bao, Jie; Weng, Hongfei; Shen, Peng; Lin, Hongbo; Chen, Wei (Frontiers in Medicine, 2022)
Purpose: To investigate the association between sleep disorders and dry eye disease (DED) in Ningbo, China. Methods: Our data came from the Yinzhou Health Information System (HIS), including 257932 patients and was based on a 1:1 matching method (sleep disorder patients vs. patients without sleep disorders) during 2013–2020. Sleep disorders and DED were identified using ICD-10 codes. Cox proportional hazards regression was used to identify the association between sleep disorders and DED. Results: The eight-year incidence of DED was significantly higher in participants with diagnosis of sleep disorders (sleep disorders: 50.66%, no sleep disorders: 16.48%, P< 0.01). Sleep disorders were positively associated with the diagnosis of DED (HR: 3.06, 95% CI: 2.99-3.13, P < 0.01)，when sex, age, hypertension, diabetes and other systemic diseases were adjusted. In the sleep disorders patients, advancing age, female sex, and presence of coexisting disease (hypertension, diabetes, hyperlipidemia, thyroid disease, depression, heart disease and arthritis) were significantly associated with the development of DED by the multivariate cox regression analysis (all P<0.05).In addition , there was a significantly positive association between estazolam and the incidence of DED in both sleep disorder and non-sleep disorder groups (all P＜0.05). Conclusions: Sleep disorder was associated with a three-time increased risk of DED. This association can be helpful in effective management of both sleep disorders and DED.